Brachypodium distachyon as a model plant toward improved biofuel crops: Search for secreted proteins involved in biogenesis and disassembly of cell wall polymers. Issue 16 (23rd July 2013) - Douché, Thibaut; Clemente, Hélène San; Burlat, Vincent; Roujol, David; Valot, Benoît; Zivy, Michel; Pont‐Lezica, Rafael; Jamet, Elisabeth
<x xml:space="preserve">Abstract</x> Polysaccharides make up about 75% of plant cell walls and can be broken down to produce sugar substrates (saccharification) from which a whole range of products can be obtained, including bioethanol. Cell walls also contain 5–10% of proteins, which could be used to tailor them for agroindustrial uses. Here we present cell wall proteomics data of Brachypodium distachyon, a model plant for temperate grasses. Leaves and culms were analyzed during active growth and at mature stage. Altogether, 559 proteins were identified by LC‐MS/MS and bioinformatics, among which 314 have predicted signal peptides. Sixty‐three proteins were shared by two organs at two developmental stages where they could play housekeeping functions. Differences were observed between organs and stages of development, especially at the level of glycoside hydrolases and oxidoreductases. Differences were also found between the known cell wall proteomes of B. distachyon, Oryza sativa, and the Arabidopsis thaliana dicot. Three glycoside hydrolases could be immunolocalized in cell walls using polyclonal antibodies against proteotypic peptides. Organ‐specific expression consistent with proteomics results could be observed as well as cell‐specific localization. Moreover, the high number of proteins of unknown function in B. distachyon cell wall proteomes opens new fields of research for monocot cell walls.